A phylogenetic study of covid-19 data from Aragon and Catalonia over a year: learning Bioinformatics during a world pandemic - Peña Bes, Fernando; García-Díaz, Álvaro; Gómez-González, Alejandro; Martín-Marcos, Adrián; Romeo, Álvaro; Sánchez-Aquilué, José Manuel; Vallés, Alba; Mayordomo Cámara, Elvira (Jornada de Jóvenes Investigadores del I3A, 2022)
We present here a one year variability analysis of SARS-CoV-2 virus in the Aragon area, comparing it to neighboring Catalonia and focusing on the UK-variant. Research was performed within a Bioinformatics course. Both a detailed assessment on the value of this methodology and novel research conclusions were extracted.